Urgency of the Regulation of No-Charge Service by Land Deed Officials (PPAT) for the Incapables - Eva Rahayu; Muktiono; Hendrarto Hadisuryo (The Islamic Education and Multiculturalism Foundation, 2023)
The obligation of Land Deed Official (PPAT) to provide services without charging a fee to someone who cannot afford it, as regulated in the Republic of Indonesia Government Regulation No.24 of 2016 concerning amendment Government Regulation No. 37 of 1998 concerning Land Deed Official (PPAT) Position Regulation, lacks restrictions in the regulation results in the blurring of norms. The need for definite regulation is necessary considering that the legal basis for providing free services is only stipulated in one article, and if interpreted, it might not be strong enough to become the basis for the implementation of the Land Deed official’s obligation. In addition to the non-regulation of standardization for the person unable to pay, another factor is that the current regulations are no longer relevant when observed from the phenomena occurring in society today. Thus, the issue in this research is the urgency of legal arrangements regarding the obligations of Land Deed Officials in providing services without charging a fee to someone who cannot afford it. The aims of this research are directed to analyze and formulate the urgency of regulation implementation as well as the legal protection provided by the government towards less privileged people. It was to determine whether the regulation remains relevant in its implementation. This research used normative legal research as a method with the Legislative Approach and Conceptual Approach.